Analysis of Application of Contract Labor Wages with Job Performance Model (Case Study on Ninja Express in Tebing Tinggi) - Santi Rohdearni Panjaitan (Institute of Computer Science (IOCS), 2022)
This study aims to determine the analysis of the application of labor wages with a job performance model (a case study on Ninja Express in Tebing Tinggi City). It can be ascertained that the salary provision is still informal, but Ninja Express has started to make a payroll system starting from job evaluation so that Ninja Express can design a fair salary structure. In addition, workers can also make consistent decisions in determining wage policies. Overall Ninja Express has provided allowances which are benefits such as health benefits such as the results of job interviews saying that Ninja Express has provided BPJS Employment benefits. Therefore, Ninja Express's workforce should use wages as an encouragement to work. In addition, the workforce always maintains or even improves performance, good performance to obtain greater achievements.